Tradisi lisan Jawa : warisan abadi budaya leluhur - Endraswara, Suwardi, 1964- (Yogyakarta : NARASI, 2005)
Oral tradition in Javanese culture
Daftar pustaka : p. 241-245
Keywords: Oral tradition -- Indonesia; Javanese (Indonesian people) -- Folklore